Formulation Development and Evaluation of Indian Propolis Hydrogel for Wound Healing - Kapare, Harshad S (2023)
Flavonoids and polyphenolic compounds play a key role in wound healing cycle modulation. Propolis, a natural bee product, has been widely reported as an enriched source of polyphenols and flavonoids as important chemical constituents and for its wound healing potential. The goal of this study was to develop and characterize a propolis-based polyvinyl alcohol (PVA) hydrogel composition with wound healing potential. To understand the impacts of critical material attributes and process parameters, formulation development was carried out using a design of experiment approach. A preliminary phytochemical analysis of Indian propolis extract showed the presence of flavonoids (23.61 ± 0.0452 mg equivalent of quercetin/g) and polyphenols (34.82 ± 0.0785 mg equivalent of gallic acid/g), both of which aid in wound healing and skin tissue regeneration. The pH, viscosity, and in vitro release of the hydrogel formulation were also studied. The burn wound healing model results revealed significant (p < 0.0001) wound contraction by propolis hydrogel (93.58 + 0.15%) with rapid re-epithelialization relative to 5% w/w povidone iodine ointment USP (Cipladine®) (95.39 + 0.16%). The excision wound healing model confirms significant (p < 0.0001) wound contraction by propolis hydrogel (91.45 + 0.29%) with accelerated re-epithelialization comparable to 5% w/w povidone iodine ointment USP (Cipladine®) (94.38 + 0.21%). The developed formulation offers promise for wound healing, which may be investigated further for clinical research.